The Genetics and Development of an Eyespot Pattern in the Butterfly Bicyclus Anynana: Response to Selection for Eyespot Shape - Monteiro, A. (1997)
The normally circular eyespots on the wing of the butterfly Bicyclus anynana were selected to become elliptical in two divergent lines, with antero-posterior elongation of the eyespots in one line and proximodistal elongation in the other. Selection was continued for nine generations, and symmetrical realized heritabilities of ~15% were achieved initially. The elliptical eyespot shapes characteristic of each line were still produced when the signaling center of the eyespot (the focus) was surgically rotated by 90 or 180° or when an eyespot was induced ectopically by localized damage. We conclude that selection changed general properties of the epidermis that responds to signals emanating from the eyespot focus but did not affect the mechanism of focal signaling.